A general, enantioselective synthesis of N-alkyl terminal aziridines and C2-functionalized azetidines via organocatalysis - Senter, Timothy J. (Tetrahedron Lett, 2015)
A short, high-yielding protocol involving the enantioselective α-chlorination of aldehydes has been developed for the enantioselective synthesis of C2-functionalized aziridines and N-alkyl terminal azetidines from a common intermediate. This methodology allows for the rapid preparation of functionalized aziridines in 50–73% overall yields and 88–94% ee, and azetidines in 22–32% overall yields and 84–92% ee. Moreover, we developed a scalable and cost-effective route to the key organocatalyst (54% overall yield, >95% dr).